A proposed ontology to support the hardware design of building inspection robot systems. (January 2023) - Ma, Leyuan; Hartmann, Timo
Abstract: Due to the growing number of architecturally complex buildings built in recent decades, mobile building inspection robot systems are required to operate in increasingly complex environments. This leads to higher requirements for their hardware design. The existing literature on the design of building inspection robots has implicitly mentioned the impact of building environments and building defects on defining robot hardware design requirements. However, the explicit representation of what information is required to define a specific hardware requirement is stimissing. To fill this gap, this paper presents an ontology that provides an overview of the building and inspection domain objects that affect the determination of robot hardware design requirements (RoboDesign). It also explores the relationship between specific robot hardware requirements and features of complex buildings and their defects. The RoboDesign ontology integrates two main domain ontology models including a Robot System Model and a Building and Defect Model. A content evaluation and an automated consistency checking are conducted for the internal evaluation of the ontology. Additionally, the proposed ontology is implemented in two wall-climbing inspection robot design cases to check if the investigation of the robot's application environment is comprehensive. The validation results also demonstrate that the use of the proposed ontological model allows to efficiently retrieve information required to determine a particular hardware requirement.